1992
DOI: 10.1002/mats.1992.040010301
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of polyelectrolyte networks induced by their interaction with an oppositely charged surfactant. Theory

Abstract: SUMMARYA very simple theory of swelling and collapse of weakly charged polyelectrolyte networks in the solution of an oppositely charged surfactant has been developed. The following contributions to the free energy were taken into account: free energy of volume interaction and of elastic deformation of the network chains, free energy connected with micelle formation and free energy of translational motion of all mobile ions in the system (translational entropy). Both the cases of a solution of charged surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
71
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 5 publications
1
71
1
Order By: Relevance
“…11 Apart from the effect of the copolymeric composition and also of the external environmental factors; surfactant-polymer interactions, especially, at the critical micelle concentration (CMC) of the surfactant affects swelling behavior of the hydrogels in a significant manner. [12][13][14][15][16] The presence of surfactants affects swelling behavior of hydrogels by micelle formation. 17 The local mobility of the surfactant molecules those enter association with the hydrogel is considerably higher than in the complex with a compact conformation, and this mobility grows with the increasing number of micelles involved in the associates.…”
Section: Introductionmentioning
confidence: 99%
“…11 Apart from the effect of the copolymeric composition and also of the external environmental factors; surfactant-polymer interactions, especially, at the critical micelle concentration (CMC) of the surfactant affects swelling behavior of the hydrogels in a significant manner. [12][13][14][15][16] The presence of surfactants affects swelling behavior of hydrogels by micelle formation. 17 The local mobility of the surfactant molecules those enter association with the hydrogel is considerably higher than in the complex with a compact conformation, and this mobility grows with the increasing number of micelles involved in the associates.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogels only slightly swelled at the CTAB concentrations lower than 10 M. The pronounced hydrogel deswelling is suggested to arise from self-assembling of the adsorbed surfactant molecules inside the hydrogel network. Due to this aggregation the concentration of mobile counterions inside the gel decreases thus reducing the internal osmotic pressure of the gel [58]. Surfactant micelles interconnecting different elastically active chains may additionally contribute to hydrogel deswelling by increasing the crosslinking density [58].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this aggregation the concentration of mobile counterions inside the gel decreases thus reducing the internal osmotic pressure of the gel [58]. Surfactant micelles interconnecting different elastically active chains may additionally contribute to hydrogel deswelling by increasing the crosslinking density [58]. The finding that these surfactant dependent hydrogel swelling are larger for the more anionic hydrogels and less for the more highly crosslinked hydrogels ( is likely due to adsorption of excessive charged surfactant molecules [59] and is dominated by increasing osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…5 Chitosan, which is a copolyInvestigations of surfactant binding in polyemer mostly of 2-amino-2-deoxy-b-D-glucopyralectrolyte networks have only more recently been nose (GLcN) and 2-acetamido-2-deoxy-b-D-glucoreported and theoretically described. [10][11][12][13] Along with the expected cooperative binding behavior, crosslinked polyelectrolyte gels generally show a 15 The degree of N-deacetylation was then 93-42). The advantages of a surfactant selective electrode in binding studies include excellent sendetermined by acid-base titration 16,17 and molecular weights were obtained by viscometry, using sitivity and reproducibility, small required sample volume, and an electrode tolerance of large the method of Wang et al 18 The chitosan polymer characteristics are reported in Table I To characterize the chitosan-SDS complex, infrared spectra were measured on a Nicolet 510P FT-IR spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%